Time-Restricted Feeding Reduces the Detrimental Effects of a High-Fat Diet, Possibly by Modulating the Circadian Rhythm of Hepatic Lipid Metabolism and Gut Microbiota - Ye, Yuqian; Xu, Haopeng; Xie, Zhibo; Wang, Lun; Sun, Yuning; Yang, Huayu; Hu, Dandan; Mao, Yilei (Frontiers in Nutrition, 2020)
Background: Time-restricted feeding, also known as intermittent fasting, can confer various beneficial effects, especially protecting against obesity and related metabolic disorders, but little is known about the underlying mechanisms. Therefore, the present study aims to investigate the effects of time-restricted feeding on the circadian rhythm of gut microbiota and hepatic metabolism. Methods: Eight-week-old male Kunming mice received either a normal diet ad libitum, a high-fat diet ad libitum, or a high-fat diet restricted to an 8-h temporal window per day for an experimental period of 8 weeks. Weight gain and calorie intake were measured weekly. Serum metabolites, hepatic sections and lipid metabolites, gut microbiota and the hepatic expression of Per1, Cry1, Bmal1, SIRT1, SREBP and PPARα were measured at the end of the experimental period. The composition of gut microbiota and the expression of hepatic genes were compared between four timepoints. Results: Mice that received a time-restricted high-fat diet had less weight gain, milder liver steatosis, and lower hepatic levels of triglycerides than mice that received a high-fat diet ad libitum (p<0.05). The numbers of Bacteroidetes and Firmicutes differed between mice that received a time-restricted high-fat diet and mice that received a high-fat diet ad libitum (p<0.05). Mice fed a time-restricted high-fat diet showed distinct circadian rhythms of hepatic expression of SIRT1, SREBP and PPARα compared with mice fed a normal diet ad libitum, as well as the circadian rhythm of the abundance of Bacteroidetes and Firmicutes. Conclusions: Time-restricted feeding is associated with better metabolic conditions, perhaps owing to alterations in gut microbiota and the circadian pattern of molecules related to hepatic lipid metabolism, which were first to report.